Effect of Acupuncture for Mixed Urinary Incontinence in Women: A Systematic Review - Long, Zilin; Chen, Huan; Yu, Shudan; Wang, Xinlu; Liu, Zhishun (Frontiers in Public Health, 2022)
Background Mixed urinary incontinence increasingly undermines women's quality of life. Previous studies showed some effects of acupuncture for MUI, but no systematic review has been done to evaluate the efficacy and safety of acupuncture for MUI in women. Objective To systematically review the efficacy and safety of acupuncture for women with MUI. Methods Ten databases (i.e., PubMed, Web of Science, Embase, ClinicalTrials.gov, the Cochrane Library, CBM, Scoups, CNKI, VIP and WANFANG DATA) were searched up to July 19th, 2021, using tailored search strategies with keywords not limited to “female,” “mixed urinary incontinence,” “acupuncture,” and “randomized controlled trial,” etc. RCTs and quasi-RCTs were included if investigating effect of any type of acupuncture for female patients with MUI. Data were extracted from eligible studies, and risks of bias were assessed according to the Cochrane Handbook from seven aspects using the RevMan 5.4 software. Results A total of three randomized studies with 591 women were included. The risk of bias among the studies varied, with major concerns on blinding of participants and outcome assessor. Liu's study (497) mainly showed that electroacupuncture's effect on reduction of numbers of incontinence, urgency, nocturia episodes, and amount of urine leakage etc. was not inferior to that of PFMT-Solifenacin group at 12, 24, and 36 weeks. Zhan's study (60) showed that electroacupuncture reduced significantly more amount of urine leakage than Tolterodine at 8 weeks, with no data on incontinence episodes frequency. All 3 studies reported that acupuncture significantly increased the quality of life assessed by ICIQ score. In addition, incidence of acupuncture-related adverse events was rare, while antimuscarinic agents related adverse events were common in two studies. Conclusion Although acupuncture showed some benefit for women with MUI, more evidences were required to draw a solid conclusion of effectiveness and safety of acupuncture for women with MUI. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO, identifier: CRD42021224600.